Building back better children's surgical services toward universal health coverage: Perspectives from Bangladesh and Zimbabwe - Mazingi, Dennis; Chowdhury, Tanvir Kabir; Aziz, Tasmiah Tahera; Tamanna, Nowrin; Lakhoo, Kokila; Banu, Tahmina; Mustafa, Saqif (Frontiers in Public Health, 2023)
Introduction Children’s surgical services are crucial, yet underappreciated, for children’s health and must be sufficiently addressed to make and sustain progress towards universal health coverage (UHC). Despite their considerable burden and socioeconomic cost, surgical diseases have been relatively neglected in favour of communicable diseases living up to their inauspicious moniker: ‘the neglected stepchild of global health’. This article aims to raise awareness around children’s surgical diseases and offers perspectives from two prototypical LMICs on strengthening surgical services in the context of health systems recovery following the COVID-19 experience to make and sustain progress towards UHC. Methods We used a focused literature review supplemented by the perspectives of local experts and the 6-components framework to present two case studies of Bangladesh and Zimbabwe. The lived experiences of the authors are used to describe the impact of COVID-19 on respective surgical systems and offer perspectives on building back the health system and recovering essential health services for sustainability and resilience. Results We found that limited high-level policy and planning instruments, an overburdened and under-resourced health and allied workforce, underdeveloped surgical infrastructure (from key utilities to essential medical products), lack of locally generated research, and the spectre of prohibitively high out-of-pocket costs for children’s surgery are common challenges in both countries that have been exacerbated by the COVID-19 pandemic. Conclusions Continued chronic underinvestment and inattention to children’s surgical diseases coupled with the devastating effect of the COVID-19 pandemic threaten the looming Lancet Commission, and progress towards UHC and Sustainable Development Goals for 2030.